2011
DOI: 10.1371/journal.pgen.1001384
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Conserved Protein Macoilin Is Required for Diverse Neuronal Functions in Caenorhabditis elegans

Abstract: Neural signals are processed in nervous systems of animals responding to variable environmental stimuli. This study shows that a novel and highly conserved protein, macoilin (MACO-1), plays an essential role in diverse neural functions in Caenorhabditis elegans. maco-1 mutants showed abnormal behaviors, including defective locomotion, thermotaxis, and chemotaxis. Expression of human macoilin in the C. elegans nervous system weakly rescued the abnormal thermotactic phenotype of the maco-1 mutants, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…(B) Pan-neuronal expression of D2092.5 (maco-1) , ortholog of macoilin, a transmembrane and coiled-coil domain-containing protein. Our data are consistent with studies published during the course of our investigation that showed neuronal-specific expression pattern for this protein and an involvement in neuronal functions in C. elegans [42], [43], motoneurons (mns) in the ventral nerve cord are indicated. (C) Neuronal-specific expression of C15C8.4, homolog of LRPAP1 a low-density lipoprotein receptor-related protein tentatively associated with degenerative dementia [77].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…(B) Pan-neuronal expression of D2092.5 (maco-1) , ortholog of macoilin, a transmembrane and coiled-coil domain-containing protein. Our data are consistent with studies published during the course of our investigation that showed neuronal-specific expression pattern for this protein and an involvement in neuronal functions in C. elegans [42], [43], motoneurons (mns) in the ventral nerve cord are indicated. (C) Neuronal-specific expression of C15C8.4, homolog of LRPAP1 a low-density lipoprotein receptor-related protein tentatively associated with degenerative dementia [77].…”
Section: Resultssupporting
confidence: 93%
“…Importantly, a number of core metazoan genes have been recently characterized (Table S3); these genes are associated with the nervous system, developmental function and human disease. For example, consistent with our expression analysis showing pan-neuronal distribution, macoilin/ maco-1 has been shown to be involved in regulating neuronal functions in C. elegans [42], [43]. Another recently characterized metazoan-specific gene is TTC19/ ddl-3 .…”
Section: Discussionsupporting
confidence: 87%
“…The worms were allowed to settle for 30 s, their movements were captured by video for 30 s, and the number of thrashing movements was counted. We also analyzed the speed of movement using a video capture system as described previously [22]. Briefly, fully matured, adult worms were transferred individually to agar plates with no food.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that MACO-1 is generally required for neuronal excitability and synapse organization 59 , 60 . FLJ10747, a predicted human homolog of MACO-1, rescued the thermotaxis defects of maco-1 mutants, 59 indicating that the function of macoilin is evolutionary conserved between nematodes and humans. Thus, the functional identifications of MACO-1 in C. elegans provided important clues for the analysis of human macoilin.…”
Section: The Usefulness Of Thermotaxis For Characterizing New Neural mentioning
confidence: 86%
“…The maco-1/ttx-8 gene, encoding a homolog of human macoilin, was originally isolated as thermotaxis defective mutant and independently as suppressor for social behavior defective mutants 59 , 60 . MACO-1 is a highly conserved novel protein with several transmembrane domains in the N-terminus and coiled-coil domains in the C-terminus.…”
Section: The Usefulness Of Thermotaxis For Characterizing New Neural mentioning
confidence: 99%